Controladoria: um estudo sobre relevância da contabilidade gerencial no processo de gestão empresarial - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The aim of this study is to analyze the relevance of management accounting to controllership in business process management, investigating the informational system generated by accounting, the application of information by controlling the economic and financial management of small and medium-sized organizations, service providers and identifying resources that managers use to decision-making, which gives opportunity a better understanding of the need for use of accounting information, highlighting a flow that shows the construction of the administrative process by managerial accounting, controllership, which operates business management and decision-making that highlights the responsibility of managers. In order to investigate how is the construction of knowledge about the management process and the method is a means to achieving a certain goal, the methodology used in this work was characterized as descriptive, because it surveys performed by through questionnaires applied to owner-managers three service providers and also the use of data collection methods, developed on the basis of evidence from scientific papers obtained and books on the subject. Based on literature searches, the study also revealed that the implementation of the three basic stages of the decision-making process (information collection, structuring and choice), is to find occasions where decisions must be taken. This work is another step in the direction of further investigations they proposed to study the functions of controlling the management of small and medium-sized service companies.
Keywords: Contabilidade gerencial; Controladoria; Gestão empresarial; Tomada de decisão; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIÊNCIAS CONTÁBEIS